Hubungan Keterampilan Sosial dengan Kecemasan Sosial pada Remaja Tunarungu - Sambodo Sriadi pinilih (AKPER Pasar Rebo, 2018)
important aspects in social and academic life in school-age children. Its physical limitations will be an internal stressor that disputes self-confidence due to disruption of self-esteem. The existence of a special learning curriculum for Children with Special Needs (ABK) consisting of 40% of academic and 60% of social skills becomes a program implemented in Wonosobo SLB. This research was descriptive correlational with cross sectional approach. The sample of this study amounted to 76 people determined were using total sampling techniqueThe purpose of the study was to find out the relationship between social skills and social anxiety. The instrument used was a questionnaire, while the data was processed by the Pearson Correlation Coefficient statistical test. The results of the study show that there is no relationship between social skills and social anxiety. The discussion of the results of the research can be done because the research subjects who are in a dormitory environment that get attention and foster sustainable social skills from caregivers and depend on peer communities with the same problems provide comfort. In conclusion, research needs to be done at the time and different data collection as a comparison.